Studies on rheology and microbiological evaluation of hydrotropically gelled starch as topical vehicle for terbinafine hydrochloride - Purushotham, Kovur; Najmuddin, M D; Satyanath, B (Asian Journal of Pharmaceutics (AJP), 2014)
The present study was aimed for the development and evaluation of hydrotropic starch gels of terbinafine hydrochloride which is an allylamine derivative of antifungal agent was formulated by using corn starch and sodium salicylate as hydrotropic salt. The gels were prepared in presence and absence of propylene glycol. The prepared gels were evaluated for in vitro drug release, rheological behavior and microbial studies. The degree of increase in the drug diffusion was found to be in order corn starch gel with propylene glycol was greater than corn starch gel without propylene glycol. The microbial studies were carried out in soya bean casein digest medium with Candida albicans as test organisms and were found to be 22.86 Â± 0.58 and 20.22 Â± 0.65 mm for TCSG (IV) and TCS (III), respectively. All the gels exhibited shear thinning. The rheogram indicated that the gel systems are pseudoplastic and exhibited thixotropy. The added propylene glycol has not appreciably altered the apparent viscosity values.